The Effect Of Benson Relaxation On Sleep Quality Among Chronic Kidney Disease Patients Undergoing Hemodialisis - Wiwit Nor Hidayati; Hepta Nur Anugrahini; Supriyanto Supriyanto; Siswari Yuniarti (Universitas Airlangga, 2026)
Introduction: Patients with chronic kidney disease (CKD) receiving hemodialysis often suffer from sleep disruptions arising from physiological alterations, emotional strain, and recurring treatment sessions. Such disruptions, if unaddressed, diminish patients' overall life satisfaction. This study aimed to determine the effect of Benson relaxation technique on sleep quality among chronic kidney disease (CKD) patients undergoing hemodialysis. Method: This study used a pre-experimental one-group pretest-posttest design. A total of 34 CKD patients undergoing routine hemodialysis were recruited using purposive sampling based on predefined inclusion and exclusion criteria. Benson relaxation was implemented twice weekly for four weeks during hemodialysis sessions. Each session lasted approximately 15 minutes and consisted of deep breathing exercises, repetition of a calming phrase, and passive relaxation until participants reported a subjective feeling of relaxation. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI). Data were analyzed using the McNemar test after categorizing PSQI scores into good and poor sleep quality categories based on the established cutoff score. Results: Pre-intervention assessments revealed universal poor sleep quality across participants. After the intervention, several participants transitioned from poor to good sleep quality. Statistical analysis via McNemar test showed a statistically significant difference in sleep quality categories after the intervention (p < 0.001). Conclusions: Benson relaxation may be considered a complementary nursing intervention that has the potential to improve sleep quality among CKD patients undergoing hemodialysis.